Exploration of the application of augmented reality technology for teaching spinal tumor’s anatomy and surgical techniques - Liu, Shuzhong; Yang, Jianxin; Jin, Hui; Liang, Annan; Zhang, Qi; Xing, Jinyi; Liu, Yong; Li, Shuangshou (Frontiers in Medicine, 2024)
Background Augmented reality (AR) technology is gradually being applied in surgical teaching as an innovative teaching method. Developing innovative teaching methods to replicate clinical theory and practical teaching scenarios, simulate preoperative planning and training for bone tumor surgery, and offer enhanced training opportunities for young physicians to acquire and apply clinical knowledge is a crucial concern that impacts the advancement of the discipline and the educational standards for young orthopedic physicians. Objective This study explores the application effect of augmented reality technology in anatomy teaching and surgical clinical teaching for spinal tumor. Methods The method utilizes virtual reality and augmented reality technology to present a spinal tumor model and the surgical process of percutaneous vertebroplasty. We conducted a random selection of 12 students forming into the augmented reality teaching group and 13 students forming into the traditional teaching group among the 8-year medical students from Peking Union Medical College and Tsinghua University, ensuring that the age and learning stage of the students in both groups were similar. Two groups of students were taught using traditional teaching methods and augmented reality technology-assisted teaching methods, respectively. A questionnaire survey was conducted after class to assess the quality of course instruction, student motivation in learning, their proficiency in anatomical structures, their comprehension of spinal tumor growth and metastasis, and their understanding and proficiency in percutaneous vertebroplasty. Results This study was the first to apply augmented reality technology in teaching, using spinal tumors and percutaneous vertebroplasty as examples, a head-mounted augmented reality device was used to create learning scenarios, presenting the complex three-dimensional spatial structure intuitively. The two groups of students differ significantly in their rating of teaching quality, enthusiasm for learning, knowledge of anatomical features, understanding of spinal trabecular structure, and understanding of steps in percutaneous vertebroplasty. The augmented reality technology-assisted teaching system demonstrates outstanding advantages. Conclusion Augmented reality technology has great potential and broad prospects in teaching bone tumors, which can help improve the visualization, interactivity, and three-dimensional spatial sense of medical teaching in spinal tumor. The application and development prospects of using augmented reality technology for anatomy instruction, surgical teaching, and simulation training are extensive.